Liquefaction analysis of marine diversion dike foundation and gravel pile reinforcement treatment based on the PL-Finn model - Jie Zhao; Yahui Lin; Yijiang Fan; Xiaodong Yu (PLoS ONE, 2025)
This study investigates the liquefaction characteristics and failure mechanisms of sand foundations in the marine diversion dike of a coastal nuclear power plant, along with the anti-liquefaction performance of gravel pile-reinforced foundations. Using the three-dimensional finite difference software FLAC3D (Fast Lagrangian Analysis of Continua), we conducted numerical simulations of both unreinforced and reinforced liquefiable sand foundations. A three-dimensional model was developed, incorporating dynamic analysis with the PL-Finn constitutive model to simulate post-liquefaction large deformations. The efficacy of compacted gravel piles was evaluated through residual deformation, excess pore water pressure, and pore pressure ratio. Results demonstrate that unreinforced foundations exhibit systematic residual deformation due to liquefaction-induced sand flow, which is significantly reduced by gravel pile reinforcement. Both excess pore water pressure and pore pressure ratio decrease markedly after reinforcement. This substantially enhances the composite foundation’s structural stability and liquefaction resistance. These findings confirm that compacted gravel pile groups provide effective drainage and anti-liquefaction capacity, meeting site liquefaction mitigation requirements under design-level ground motion intensity, thereby offering a reference for similar engineering projects.